Arabic Gender Podcasts: A Genre Analysis of Content, Forms, and Agendas Challenging Traditional Narratives - ghosn, zeinab (AUC Knowledge Fountain, 2024)
This thesis examines the genre forms and agendas of Arabic gender podcasts through qualitative analysis of 100 episodes from 20 podcasts combined with creator interviews. The research reveals distinctive cultural adaptations of global podcast formats, characterized by a preference for co-hosted (46%) and panel discussion (32%) formats over solo hosting. This adaptation creates intimate spaces for challenging traditional gender narratives through advocacy (24%), education (23%), and empowerment (21%) content genres. The study introduces the concept of “cultural genre adaptation” in podcasting and proposes a “layered agenda-setting” model that extends McCombs' traditional theory. The findings demonstrate how Arabic gender podcasts maintain cultural sensitivity while advancing progressive gender discourse. A key aspect of this is the careful crafting of parasocial relationships, which helps the audience feel connected and engaged. While the study's scope is limited by the technical difficulty in obtaining a comprehensive list of Arabic gender podcasts and the frequent discontinuation of shows, affecting sample representativeness, this research contributes to understanding the intersection of podcasting, gender studies, and cultural adaptation in digital media, particularly in the Arab context. The results suggest an integrated model showing how podcast genres evolve through cultural specificity rather than purely technological affordances.